Teacher educators and environmental justice: conversations about education for environmental justice between science and geography teacher educators based in England and Brazil - Gandolfi, Haira E.; Rushton, Elizabeth A. C.; Silva, Luciano Fernandes; da Silva Carvalho, Maria Bernadete Sarti [UNESP] (My University, 2024)
While environmental education has been present in the field of education for decades now, only recently our particular subject areas of science and geography have started to pay more critical attention to specific concerns surrounding the intersection of environmental issues and social justice (also known as environmental justice) within the context of formal secondary education, including in secondary teacher education programmes. Drawing on scholarship, policy landscapes and socio-environmental concerns from both the global South and the global North, and on a methodological approach based on transnational collective reflection and collaborative-dialogic writing, in this article we delve into our different cultural, geographical and disciplinary contexts, views and experiences as four teacher educators from Brazil and England who have been working at this intersection between environmental justice and Science and Geography teacher education programmes for secondary formal education. Here we will argue that environmental justice needs to have a central role in such teacher education programmes if we aim to support young people and their teachers in navigating the spatially diverse and unequal impacts of environmental emergencies in global North and South communities. We also consider future directions for research and collaboration across national and disciplinary boundaries within the landscape of environmental education for environmental justice, reflecting on the future of teacher education across the global North and the global South when facing more frequent and severe environmental emergencies.
Keywords: Environmental education; Environmental justice; Teacher education; Teacher educators